2011
DOI: 10.3109/09537104.2011.584086
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume/platelet count ratio as a predictor of long-term mortality after non-ST-elevation myocardial infarction

Abstract: Previous studies reported an association between elevated mean platelet volume (MPV) and post-myocardial infarction mortality. This study explores the association between long-term mortality after non-ST-segment elevation myocardial infarction (NSTEMI) and the peripheral blood platelet indices (i.e., the mean platelet volume (MPV), platelet count, and the MPV/platelet (MPV/P) ratio). Two physicians independently reviewed the data of 619 NSTEMI patients. The blood samples were drawn and analyzed within 1 h of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
98
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 36 publications
5
98
3
Order By: Relevance
“…Although increased endogenous erythropoietin may play a role in thrombocytosis, mechanism of platelet production in irondeficiency induced thrombocytosis is yet to be fully understood and relevant platelet indices are not fully evaluated [5]. Recently, mean platelet volume (MPV) has been suggested as a useful platelet index for platelet function and activation [5][6][7][8][9][10]. Also, MPV/platelet count ratio has been proposed as a new parameter for the prediction of long-term mortality in patients with myocardial infarction [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although increased endogenous erythropoietin may play a role in thrombocytosis, mechanism of platelet production in irondeficiency induced thrombocytosis is yet to be fully understood and relevant platelet indices are not fully evaluated [5]. Recently, mean platelet volume (MPV) has been suggested as a useful platelet index for platelet function and activation [5][6][7][8][9][10]. Also, MPV/platelet count ratio has been proposed as a new parameter for the prediction of long-term mortality in patients with myocardial infarction [9].…”
mentioning
confidence: 99%
“…Recently, mean platelet volume (MPV) has been suggested as a useful platelet index for platelet function and activation [5][6][7][8][9][10]. Also, MPV/platelet count ratio has been proposed as a new parameter for the prediction of long-term mortality in patients with myocardial infarction [9]. In this context, we planned to investigate MPV and MPV/platelet count ratio according to serum iron status in patients with anemia.…”
mentioning
confidence: 99%
“…Based on these aforementioned data, the authors of these studies claimed that one of the mechanisms responsible for bad cardiovascular outcomes in higher inflammatory state may be impairment in coronary collateralization. Furthermore, MPV has been shown to be associated with atherosclerosis, coronary events, and bad prognosis in numerous studies [6][7][8][9]. Similarly, based on the article of Ege et al [1], it can be speculated that the association between higher MPV and bad prognosis may be partly due to poor collateral development.…”
Section: 1mentioning
confidence: 97%
“…Some other recent studies have reported that an elevated MPV is linked with peripheral artery disease and stroke, all of which are related to atherosclerosis on the basis of inflammation [5]. Previous studies demonstrated an association between long-term mortality after non-ST-segment elevation myocardial infarction and peripheral blood platelet indices including MPV and platelet count [12]. The MPV can also be affected by thyroid and rheumatic diseases [13,14], malignancy and medications such as anticoagulant therapy and statins.…”
mentioning
confidence: 99%